Neutropenic enterocolitis secondary to propylthiouracil-induced agranulocytosis - Erdem Barış Cartı; Erkan Oymacı; Ahmet Deniz Uçar; Ali Coşkun; Nazif Erkan; Mehmet Yıldırım (Turkish Journal of Gastroenterology, 2019)
-